Alterations in Intramedullary T2-weighted Increased Signal Intensity following Laminoplasty in Cervical Spondylotic Myelopathy Patients: Comparison Between Pre- and Postoperative Magnetic Resonance Images. Issue 22 (15th November 2018) - Machino, Masaaki; Ando, Kei; Kobayashi, Kazuyoshi; Ito, Kenyu; Tsushima, Mikito; Morozumi, Masayoshi; Tanaka, Satoshi; Ota, Kyotaro; Ito, Keigo; Kato, Fumihiko; Ishiguro, Naoki; Imagama, Shiro
Abstract : Study Design: A prospective comparative imaging study. Objective: This study investigated whether the postoperative classification of and alterations in increased signal intensity (ISI) of the spinal cord reflected the postoperative severity of symptoms and surgical outcomes in cervical spondylotic myelopathy (CSM) patients. Summary of Background Data: Although ISI on performing magnetic resonance imaging (MRI) is observed in CSM patients, alterations in ISI have not been investigated. The association of postoperative ISI with surgical outcomes in CSM patients remains controversial. Methods: Totally, 505 consecutive CSM patients (311 males) with a mean age of 66.6 (range, 41–91) years were enrolled. All were treated with laminoplasty and underwent MRI scans: preoperatively and after an average of 26.5 months postoperatively (range 12–66 months). ISI was classified pre- and postoperatively into three groups based on sagittal T2-weighted magnetic resonance images: Grade 0, none; Grade 1, light (obscure); and Grade 2, intense (bright). The patients' pre- and postoperative neurological statuses were evaluated using the Japanese Orthopaedic Association scoring system for cervical myelopathy (JOA score) and other quantifiable tests, including the 10-s grip and release (10-s G&R) test and 10-s step test. Results: Preoperatively, 168 patients had Grade 0 ISI, 169 had Grade 1, and 168 had Grade 2; postoperatively, 210 patients had Grade 0 ISI, 94 had Grade 1, and 201 had Grade 2. Patients with postoperative Grade 0 ISI had a better postoperative JOA score, recovery rate, and 10-s G&R and 10-s step test scores than those with other grades. The postoperative ISI grade improved in 66 patients (13.1%), worsened in 57 (11.3%), and remained unchanged in 382 (75.6%). Conclusion: Postoperative ISI partially reflects postoperative symptoms and surgical outcomes. Alterations in ISI were observed postoperatively in 123 patients (24.4%) and were not correlated with surgical outcomes. Level of Evidence: 2